Rancang Bangun Prototipe Dan Aplikasi Android Qrcode Mobile Parking Berbasis Arduino - Prayoga, Dicky; Simanjuntak, Pastima (UNIVERSITAS PELITA HARAPAN, 2020)
Abstract– With the progress of the development of the technological world in the present Android-based application now has its own attraction to its features and is a choice for its users as a medium of information or for communication, by gaining personal benefits and mutual benefits in the creation of applications that help human activity For example, in online sales or applications that can connect with other people that are located far enough away so that by using applications such as Whatsapp, Messenger, BlackBerry Messenger, we can interact directly with looking at the face by utilizing the videocall feature provided by the application. With the QRcode mobile parking application that has been made by researchers this time with the market needs to facilitate human work in daily activities by utilizing technology that has been growing rapidly, with this application so as to minimize the occurrence of losses or unwanted events, such as saving the use of paper in transactions in and out of vehicles that will enter or exit the parking area, or the occurrence of jams that occur at certain hours such as if the usual used parking paper runs out, so it requires time to replace or add to the finished paper, and Not a few drivers who are provoked to see the congestion that occurs, the increasingly chaotic conditions can make motorists cancel their visit to tourist attractions or shopping centers that still use parking tickets, so that there can be losses for the tour management a or building manager with a reduced number of visitors who come.Keywords: Arduino Uno, Android Studio, MIT App Inventor, Qrcode